Systematic Review: Efektivitas Bobath Exercise Pada Cerebral Palsy Spastik Diplegi - Dela Fariha Fuadi; Suminarti Suminarti (Indonesian Journal of Health Science, 2022)
Cerebral Palsy (CP) is a motor development disorder in children caused by damage to the brain that occurs in the period before, after, and during birth which is characterized by weakness in the upper limbs, with high postural muscle tone characteristics. Bobath is a method that is often used as a therapy for children with cerebral palsy. This article aims to determine the effectiveness of bobath training on diplegic cerebral palsy patients. The method used in the preparation of this article is by searching articles through Google Scholar and Pubmed. The inclusion criteria of the selected articles were in the form of experimental studies on patients with CP Diplegia. The number of articles selected based on the search results and article selection is 10. Giving exercise therapy using the bobath method helps improve children's functional activities in improving postural control, GMFM, and the effectiveness of muscle contractions through EMG. Cerebral Palsy (CP) merupakan suatu gangguan tumbuh kembang motorik anak yang disebabkan adanya kerusakan pada otak yang terjadi pada periode sebelum, sesudah, dan selama kelahiran yang ditandai dengan kelemahan pada anggota gerak atas, dengan karakteristik tonus postural otot yang tinggi. Bobath merupakan salah satu metode yang sampai saat ini sering digunakan sebagai terapi pada anak dengan cerebral palsy. Artikel ini bertujuan untuk mengetahui efektivitas dari latihan bobath terhadap pasien cerebral palsy diplegi. Metode yang digunakan dalam penyusunan artikel ini adalah dengan penelusuran artikel melalui google scholar dan pubmed. Kriteria inklusi dari artikel yang dipilih adalah berupa penelitian experimen pada pasien CP Diplegia. Jumlah artikel yang dipilih berdasarkan hasil penelusuran dan seleksi artikel adalah berjumlah 10. Pemberian terapi latihan dengan metode bobath membantu meningkatkan aktifitas fungsional anak dalam meningkatkan postural control, GMFM, efektivitas kontraksi otot melalui EMG.